Kepastian Hukum Pemberian Hak Guna Bangunan Kepada Persekutuan Komanditer - Marchelo Ivan Darmawan; Andita Atmajaya; Oktafi Mar’atul Mashfufah (JURNAL RECHTENS, 2026)
The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) issued a policy in the form of Circular Letter Number 2/SE-HT.02.01/VI/2019 dated June 28, 2019, concerning the granting of Right to Build (Hak Guna Bangunan or HGB) titles to Limited Partnerships (Commanditaire Vennootschap or CV). One of the key provisions therein establishes that a CV is eligible to submit an application for land rights in the form of an HGB. This policy has subsequently given rise to challenges regarding its implementation. The objective of this research is to provide a comprehensive comparison necessary for analyzing the legal certainty of granting HGB titles to CVs, particularly by referencing the Netherlands—a country adhering to the same Civil Law system—which also recognizes the CV business entity form within its corporate legal framework. The research methodology employed in this study is normative juridical research. The findings of this research indicate that the granting of HGB titles to Limited Partnerships (CV) does not satisfy the principle of legal certainty, as its legal basis—governed by Circular Letter Number 2/SE-HT.02.01/VI/2019—contravenes higher statutory regulations. This legal uncertainty impacts the general public and business actors, who frequently face ambiguity regarding the legal status of the land they possess. Furthermore, this situation not only constitutes a violation of agrarian law but also creates the potential for future land disputes.